Gene Expression and Proteomics Studies Suggest an Involvement of Multiple Pathways Under Day and Day–Night Combined Heat Stresses During Grain Filling in Wheat - Chunduri, Venkatesh; Kaur, Amandeep; Kaur, Shubhpreet; Kumar, Aman; Sharma, Saloni; Sharma, Natasha; Singh, Pargat; Kapoor, Payal; Kaur, Satveer; Kumari, Anita; Roy, Joy; Kaur, Jaspreet; et al. (Frontiers in Plant Science, 2021)
Recent weather fluctuations imposing heat stress at the time of wheat grain filling cause frequent losses in grain yield and quality. Field-based studies for understanding the effect of terminal heat stress on wheat are complicated by the effect of multiple confounding variables. In the present study, the effect of day and day–night combined heat stresses during the grain-filling stage was studied using gene expression and proteomics approaches. The gene expression analysis was performed by using real-time quantitative PCR (RT-qPCR). The expression of genes related to the starch biosynthetic pathway, starch transporters, transcription factors, and stress-responsive and storage proteins, at four different grain developmental stages, indicated the involvement of multiple pathways. Under the controlled conditions, their expression was observed until 28 days after anthesis (DAA). However, under the day stress and day–night stress, the expression of genes was initiated earlier and was observed until 14 DAA and 7 DAA, respectively. The protein profiles generated using two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) and matrix-assisted laser desorption/ionization time-of-flight mass spectroscopy (MALDI-TOF MS/MS) showed a differential expression of the proteins belonging to multiple pathways that included the upregulation of proteins related to the translation, gliadins, and low-molecular-weight (LMW) glutenins and the downregulation of proteins related to the glycolysis, photosynthesis, defense, and high-molecular-weight (HMW) glutenins. Overall, the defense response to the day heat stress caused early gene expression and day–night heat stress caused suppression of gene expression by activating multiple pathways, which ultimately led to the reduction in grain-filling duration, grain weight, yield, and processing quality.